PENGARUH PENGGUNAAN SUMBER BELAJAR BERBASIS BUKU TEKS TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS TERPADU - Tolingguhu, Karsum; Panigoro, Meyko; Bahsoan, Agil; Mahmud, Melizubaida; Toralawe, Yulianti (Universitas Negeri Gorontalo, 2024)
Student learning outcomes in social studies subjects are still low, then there is still a lack of development of learning resources by teachers to students so that students are less motivated to learn. The study aimed to determine the extent of the influence of using textbook-based learning resources on students' learning outcomes in Integrated Social Sciences subject for Grade VIII at SMP Negeri 1 Tomilito, North Gorontalo Regency. The research adopted a quantitative approach, with a correlational quantitative method with a sample size of 45 students. Data collection techniques used in this study included observation, questionnaires, documentation, and data analysis techniques using simple regression in the research. The research findings indicated a positive and significant influence between the use of textbook-based learning resources and students' learning outcomes in Integrated Social Sciences subject for Grade VIII at SMP Negeri 1 Tomilito, North Gorontalo Regency. The coefficient of determination of the regression model previously obtained was 0,237, meaning that 23,7% of the variation in learning outcomes is explained by using textbook-based learning resources in the learning activities. In other words, the better the use of textbook-based learning resources by teachers, the higher the students' learning outcomes. The value of students' outcomes or influence by other variables not examined in 76,3%.